Evaluación de materiales en la zona de la sabana de Bogotá como medios filtrantes para aguas residuales - Espinosa García, Helmut; Hernández Montaña, Vilma; Lozano Puentes, Nelly P.; Tavera Tavera, Johana; Cervera Bonilla, Alexis; Granja Rodríguez, Adriana; Yagüará, Didier (Revista Científica, 2011)
The intention of the investigation was centered in the evaluation and comparison of conventional and non conventional filter materials in percolators residual water filters, for which tests were made in a modulate experimental on the superficial hydric body of the river Padre Jesus in Bogotá D.C. The evaluation was made considering the parameters physical-chemistries of quality of the effluent, in special the quality of the DQO and the conformation of biofilm.